Vaccination status and outcomes of COVID‐19 patients admitted to a tertiary hospital in Iran during the dominant Delta variant period - Hamed Mehdinezhad; Bardia Karim; Niloufar Ahmadi; Reza Mohseni Ahangar; Ali Asadolahzadeh; Mahmoud Sadeghi Haddad‐Zavareh; Fatemeh khoshkhou; Zeynab Qolami; Neda Mahdinezhad Gorji; Mouloud Agajani Delavar (Immunity, Inflammation and Disease, 2023)
Abstract Background This study aimed to determine the characteristics, vaccination status, and outcomes of confidence interval (COVID‐19) patients, admitted to a tertiary hospital in Iran during the predominant severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) Delta variant period. Methods This retrospective study assessed the medical records of all hospitalized COVID‐19 patients, who were admitted to a tertiary hospital from July 10 to September 15, 2021. Adjusted binary logistic regression analyses were conducted to determine factors associated with poor outcomes. Results More than 25% of hospitalized patients received at least one vaccine dose of SARS‐CoV‐2. The Sinopharm BIBP vaccine (China) was the most commonly received vaccine (73.3%). After adjusting for age and comorbidities, the adjusted odds ratio (AOR) for poor outcomes was significantly lower in hospitalized patients who received Remdesivir compared to those not receiving Remdesivir (AOR: 0.35; 95% confidence interval [CI]: 0.15, 0.78; p < .010). Besides, age ≥50 years (AOR: 2.51; 95% CI: 1.38, 4.59; p < .003), low educational level (AOR: 3.99; 95% CI: 1.17, 13.53; p < .027), work outside in the past year (AOR: 1.75; 95% CI: 1.02, 3.00; p < .041), and diabetes mellitus (AOR: 1.95; 95% CI: 1.66, 3.26; p = .011) were associated with more poor outcomes. Conclusion Based on the present results, the risk of mortality and the risk of poor outcomes were lower in patients who received Remdesivir compared to those not receiving Remdesivir. The number of vaccinated patients was smaller than the unvaccinated among hospitalized patients. It is important to emphasize that vaccination reduced the need for hospitalization and that only vaccinated patients with comorbidities required hospitalization.